Relevância do VANT no processo de representação e produção de Arquitetura - Antunes, J. (2020)
The emergence of the airplane as an influential element for architects of the twentieth century’s modern movement, has transformed the knowledge and modes of interpreting the landscape, which has a reflection in planning and interacting with the territory. In the 21st Century, the relevance of the aircraft is perpetuated with the emergence of the Unmanned Aerial Vehicles (UAV) - commonly designated as drones - in the airspace of the city. The democratization of this technology transforms the urban airspace, promoting a paradigm shift from contemporary reality and influencing aspects such as privacy, security, urban planning and regulations of airspace utilization. On the professional scope, the relevance of the UAV in the process of representing and producing Architecture becomes one of its most influential points by enabling new forms of action by the architect and expanding his autonomy, technical capacity and awareness of the scenarios where he intervenes. With the aim of framing the relevance of these vehicles in the process of representation and production of architecture, this work exposes the main valences of UAVs in architecture, by investigating their specifications and applications in different areas. The development of a case study with a UAV and aerial digital photogrammetry made it possible to test the developed premises.